Odpowiedzi

2010-02-16T19:29:05+01:00
A)12:m=1/4
m=12*1/4
m=3

b)x*3 i 1/2=2/7
x=7/2:2/7
x=49/4 = 12 i 1/4

c)12 i 1/3+ k= 16 i 5/6
k=16i5/6-12 i 1/3
k=16 i 5/6- 12 i 2/6
k=4 i 3/6= 4 i 1/3

d) 8 i 1/5 + c= 10 i 7/10
c=10 i 7/10 - 8 i 1/5
c=10 i 7/10 - 8 i 2/10
c=107/10-82/10
c=25/10= 2 i 5/10= 2 i 1/2

e) 4 i 2/3 *=4
o czymś zapomniałaś
f) a: 1 i 1/3 = 1/6
a=1/6*1 i 1/3
a=1/6*4/3
a=2/9

Pozdrzawiam
3 5 3
2010-02-16T19:40:23+01:00
A)
12:m=1/4
m=12*1/4
m=48

b)
x*3 i 1/2=2/7
x=2/7:3,5
x=4/49

c)
12 i 1/3+ k= 16 i 5/6
k=16⁵/₆-12⅓
k=4⅓

d)
8 i 1/5 + c= 10 i 7/10
c=10⁷/₁₀-8⅕
c=2,5

e)
4 i 2/3 *a=4
a=4:4⅔
a=6/7

f)
a: 1 i 1/3 = 1/6
a=1/6*1⅓
a=2/9
4 2 4